Women in Science: A Student Workshop at a University in Mexico - Daniela C. González Cruz; Sofía Jezzini Martínez; Paloma Calafia Leyva Camacho; Ilse Janeth De la Rosa-Rodríguez; Andrea Flores Rodríguez; Karina Raygoza Cortez; Mariana García Leal (University Library System, University of Pittsburgh, 2023)
Women have participated in science since the earliest of times. However, their valuable contributions are not as widely acknowledged throughout our history and women still face several barriers throughout their professional career. We developed and hosted a half-day Women in Science seminar organized by students, for students. The main goal was to promote ways to involve more women in research activities and to strengthen the scientific community within our medical school. The workshop consisted of three main sections, where we shared relevant statistics, resources, and strategies among a community of students interested in science. At the end of the workshop, participants shared their insights proving the necessity and utility of such events to strengthen the development of science as an inclusive field.